2024
DOI: 10.1038/s41598-023-50722-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram for predicting in-hospital mortality of patients with acute paraquat poisoning

Guo Tang,
Zhen Jiang,
Lingjie Xu
et al.

Abstract: This study aimed to develop and validate a predictive model to determine the risk of in-hospital mortality in patients with acute paraquat poisoning. This retrospective observational cohort study included 724 patients with acute paraquat poisoning whose clinical data were collected within 24 h of admission. The primary outcome was in-hospital mortality. Patients were randomly divided into training and validation cohorts (7/3 ratio). In the training cohort, the least absolute shrinkage and selection operator re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(62 reference statements)
0
2
0
Order By: Relevance
“… 6 At present, there are no standardized methods for predicting the outcomes in patients with PP. 8 However, a recent study showed that decreased consciousness level with (Glasgow coma scale <15), high neutrophil-to-lymphocyte ratio (>18), alanine aminotransferase (>40 IU/L), and creatinine (>1.24 mg/dL) apart from high paraquat plasma concentrations at admission (>11.5 gm/mL) were identified as independent predictors of in-hospital mortality in patients with acute PP. 8 Previous literature also revealed that liver and renal dysfunction, serum anion gap above 25.5 mmoL/L, and computerized tomography of the thorax were predictors of outcomes in PP.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“… 6 At present, there are no standardized methods for predicting the outcomes in patients with PP. 8 However, a recent study showed that decreased consciousness level with (Glasgow coma scale <15), high neutrophil-to-lymphocyte ratio (>18), alanine aminotransferase (>40 IU/L), and creatinine (>1.24 mg/dL) apart from high paraquat plasma concentrations at admission (>11.5 gm/mL) were identified as independent predictors of in-hospital mortality in patients with acute PP. 8 Previous literature also revealed that liver and renal dysfunction, serum anion gap above 25.5 mmoL/L, and computerized tomography of the thorax were predictors of outcomes in PP.…”
Section: Introductionmentioning
confidence: 95%
“…8 However, a recent study showed that decreased consciousness level with (Glasgow coma scale <15), high neutrophil-to-lymphocyte ratio (>18), alanine aminotransferase (>40 IU/L), and creatinine (>1.24 mg/dL) apart from high paraquat plasma concentrations at admission (>11.5 gm/mL) were identified as independent predictors of in-hospital mortality in patients with acute PP. 8 Previous literature also revealed that liver and renal dysfunction, serum anion gap above 25.5 mmoL/L, and computerized tomography of the thorax were predictors of outcomes in PP. 9,10 We aimed to explore parameters correlating with the mortality in patients with PP in the first 48 hours of hospitalization and the utility of the SOFA score as a predictor of mortality within 24 hours of ICU admission.…”
Section: Introductionmentioning
confidence: 95%